(untitled) (International Educators Conference, 2025)
This article explores the influence of superstitions on the engagement of young school-aged children in play and study. It examines how cultural beliefs and superstitious practices may shape students’ motivation, behavior, and academic performance. Through a mixed-methods approach, the study analyzes existing literature, surveys educators, and observes student behavior to understand the interplay between superstitions and learning environments. The findings suggest that superstitions can both positively and negatively affect student interest, depending on their context and application.